Pengaruh Rekrutmen dan Promosi Jabatan terhadap Kinerja Karyawan pada PT. Jambi Wood Industri - Akhmadi Akhmadi; Jasasila Jasasila (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
One of the activities in HR management is the recruitment and promotion of positions. Recruitment is a process of gathering a number of applicants who have qualifications in accordance with what is needed by the company, to be employed company (Malthis, 2001). The benefits of recruitment is to have the function of "the Right Person in the Right Place", where this becomes a guide for managers in at the placing the existing workforce in the company. PT. Jambi Wood Industry is a company engaged in the processing of semi-finished wood. Reliable and competent human resources are the lever factor for PT. Jambi Wood Industry, so the development of Human Resources Competence is one of the key factors that succeed. Based on the Effect of Recruitment and Job Promotion on Employee Performance at PT Jambi Wood Industri, Rantau Puri Village. Where Recruitment with t count of 2.632> t table 1.678. and. Job Promotion with t count 9.096> t table 1.678. Job Promotion Optimizes Employee Performance at PT Jambi Wood Industri Desa Rantau Puri. At the level of confidence (α = 0.05) and df 2: 47 obtained f table value of 3.20 through the calculated f value of 51.341. Relating to Recruitment and Promotion of Positions together on Employee Performance